2007
DOI: 10.1016/j.ijpara.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Nimbus (BgI): An active non-LTR retrotransposon of the Schistosoma mansoni snail host Biomphalaria glabrata

Abstract: The freshwater snail Biomphalaria glabrata is closely associated with the transmission of human schistosomiasis. An ecologically sound method has been proposed to control schistosomiasis using genetically modified snails to displace endemic, susceptible ones. To assess the viability of this form of biological control, studies towards understanding the molecular makeup of the snail relative to the presence of endogenous mobile genetic elements are being undertaken since they can be exploited for genetic transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 53 publications
(74 reference statements)
2
22
0
Order By: Relevance
“…To determine whether the kinetics of nimbus RT induction coincides with that of Hsp 70 following exposure to either normal or attenuated miracidia, we examined the expression of the nimbus RT transcript (Raghavan, et al, 2003, Raghavan, et al, 2007) in the RNA samples described above. Susceptible snails exposed 5 hours to normal miracidia showed a significant increase (28.9 fold) in nimbus RT with a steady decrease (26.51 to 12.49 fold) in the levels of expression between 10 to 48 hours post-exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether the kinetics of nimbus RT induction coincides with that of Hsp 70 following exposure to either normal or attenuated miracidia, we examined the expression of the nimbus RT transcript (Raghavan, et al, 2003, Raghavan, et al, 2007) in the RNA samples described above. Susceptible snails exposed 5 hours to normal miracidia showed a significant increase (28.9 fold) in nimbus RT with a steady decrease (26.51 to 12.49 fold) in the levels of expression between 10 to 48 hours post-exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To resolve this uncertainty regarding the differential gene expression of Hsp 70 between resistant and susceptible snails, especially during early time points when subjected to stress from heat shock (abiotic stress) and following parasite (biotic stress) infection, we decided to further examine the differential Hsp 70 induction in parasite resistant vs susceptible juvenile snails before and after either heat shock or infection. In addition, modulation of the reverse transcriptase (RT) encoding domain of the snail non-LTR retrotransposon, nimbus , in relation to stress (heat shock and infection) was also investigated (Raghavan, et al, 2003, Raghavan, et al, 2007). Mobile genetic elements (MGEs), such as non-LTR-retrotransposons have been shown to be activated by pathogens, environmental stress, and wounding (Mhiri, et al, 1997, Wessler, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, currently available data in the public domain for the B. glabrata genome shows that aside from its inherent repetitive nature it also contains different types of mobile genetic elements. We previously characterised one of these elements, the non-long terminal repeat (LTR) retrotransposon, nimbus (Raghavan et al, 2007), and have since shown that the reverse transcriptase (RT) domain of this element is co-transcribed with the stress gene, Hsp 70, early in susceptible juvenile snails (NMRI and M-line) after S. mansoni infection (Ittiprasert et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…To better qualify for full genome sequencing, some research communities developed complementary genomic resources. Bacterial artificial chromosome (BAC) libraries were developed for several molluscs like B. glabrata (Gastropda) and the oysters Crassostrea virginica and C. gigas , to gain initial access to genomic information (Adema et al, 2006; Cunningham et al, 2006; Raghavan et al, 2007). BAC libraries consist of considerable numbers of clones that represent the full genome with large (>100kb) inserts of molluscan genomic DNA.…”
Section: Genomes and Next-generation Sequencing Immunogenomics Phmentioning
confidence: 99%